Magnetic control nano ferrocobalt-based environment-friendly material as well as preparation method and application thereof
Preparing magnetically controlled nano-cobalt-iron-based environmentally friendly materials through the rheological phase method solves the problem that traditional methods are difficult to efficiently treat cobalt-containing wastewater, and achieves efficient and low-cost wastewater treatment and resource recycling.
Patent Information
- Application Number
- CN202411520562.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The prior art is difficult to efficiently and at low cost to treat cobalt-containing wastewater, and traditional methods pose safety risks and environmental hazards.
The use of the current -based magnetic control nano -cobalt iron -based environmental protection materials, using low sub -sulfate solution as a reducing agent to generate nano -zero -price iron material, and restore it under liquid phase conditions. Sexual magnetic nanow -cobalt iron -based environmental protection materials.
A cobalt -containing wastewater treatment of high -efficiency and low cost can be achieved, which can significantly degrade organic matter and realize the recycling of cobalt and iron, reducing the cost of treatment and environmental burden.
Smart Images

Figure CN119332089A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic nanomaterials, and relates to a magnetically controlled nano cobalt-iron-based environmentally friendly material, a preparation method and an application thereof, and in particular to a magnetically controlled nano cobalt-iron-based environmentally friendly material, a preparation method thereof, and an application thereof in the treatment of cobalt-containing wastewater recovery and the treatment of antibiotics. Background Art
[0002] The sources of cobalt-containing wastewater can be mainly attributed to the following aspects: Lithium battery production: Cobalt-containing wastewater mainly comes from the production process of lithium battery materials such as cobalt tetroxide. In this process, raw materials such as cobalt chloride crystals, ammonium bicarbonate crystals and pure water generate target products through specific chemical reactions (such as CoCl2+2NH4HCO3→CoCO3↓+2NH4Cl+CO2↑), and are accompanied by a variety of wastewaters, including but not limited to cobalt tetrachloride mother liquor, cobalt tetrachloride washing water, acid and alkali wastewater, copper and manganese precipitation wastewater, cobalt salt wastewater, ammonium chloride wastewater and cobalt oxide process wastewater. In addition, daily equipment cleaning and clean floor maintenance will also contribute a certain amount of cobalt-containing wastewater. In the electroplating industry, cobalt, as part of the electroplating solution, will produce wastewater containing cobalt ions during the use of the electroplating process. In the production process of ceramic products, especially the production of certain special ceramics (such as ceramic pigments or glazes containing cobalt elements), cobalt-containing wastewater may also be generated. In addition to the above-mentioned main industrial production processes, cobalt-containing wastewater may also come from other fields, such as metal smelting, chemical production, etc. These fields may use cobalt or its compounds in the production process, thereby generating cobalt-containing wastewater.
[0003] In summary, the sources of cobalt-containing wastewater are extensive, mainly involving the production processes of lithium batteries, electroplating, ceramics and other industries. These wastewaters usually contain high concentrations of cobalt ions, as well as possible accompanying organic matter, heavy metal ions and other harmful substances, posing a potential threat to the environment and human health. Therefore, the effective treatment of cobalt-containing wastewater is particularly important.
[0004] Cobalt-iron alloys have unique soft magnetic material properties such as high saturation magnetization, high Curie temperature, low coercivity, high magnetic permeability and low magnetic anisotropy constant. As a key magnetic nanomaterial, they have been widely used in strategic fields such as aviation generators, computer read-write heads, micro-electromechanical systems (MEMS), magnetic keys and the automotive industry. Due to the quantum size effect, these materials show broad application prospects in the fields of magnetism, catalysis and electromagnetic wave absorption.
[0005] Therefore, there is a need for a magnetically controlled nano-cobalt-iron-based environmentally friendly material that can efficiently and low-cost treat cobalt-containing wastewater, in order to achieve the degradation of organic matter in the cobalt-containing wastewater and the recycling of cobalt and iron. Summary of the invention
[0006] In view of this, the present invention provides a magnetically controlled nano-cobalt-iron-based environmentally friendly material and a preparation method and application thereof. The preparation method utilizes a rheological phase method and uses an environmentally compatible low-sulfite solution as a reducing agent to prepare a nano-zero-valent iron environmentally friendly material. The prepared nano-iron material is used as a reducing agent and is reduced under liquid phase conditions to obtain a magnetically controlled nano-cobalt-iron-based environmentally friendly material. The material not only has extremely high organic matter degradation performance, but also has good environmental friendliness, and can achieve more efficient and low-cost removal and wastewater purification, and is used to treat and recover cobalt-containing wastewater.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a magnetically controlled nano-cobalt-iron-based environmentally friendly material comprises the following steps:
[0009] S1: In a glove box, sodium hydroxide powder, sodium dithionite and ferrous salt are taken, mixed evenly to obtain a solid mixture, and deionized water is sprayed. The mass ratio of sodium hydroxide powder, sodium dithionite and ferrous salt is 1~2:1~2:1, and the mass ratio of deionized water to the solid mixture is 0.3~0.5:1. Nano-zero-valent iron is obtained under rheological phase conditions;
[0010] S2: In a water bath, pass nitrogen for 30 min, add cobalt chloride hexahydrate, stir mechanically to fully dissolve, add nano zero-valent iron prepared in step S1, the mass ratio of cobalt chloride hexahydrate to nano zero-valent iron is 4-5:1, keep heating and stirring to ensure that the cobalt salt is fully reduced by iron;
[0011] S3: After the reaction is complete, stirring is stopped, the cobalt salt reaction product that has been fully reduced by iron in step S2 is allowed to stand and cool to room temperature, and then filtered under nitrogen protection, the separated solid product is washed, repeatedly ultrasonically cleaned until neutral, and vacuum dried to obtain a layered magnetically controlled nano-cobalt-iron-based environmentally friendly material;
[0012] S4: placing the magnetically controlled nano-cobalt-iron-based environmentally friendly material prepared in step S3 in an external magnetic field with a magnetic field strength of 300-800 kA / m to achieve separation of cobalt and iron, and further achieve magnetic recycling.
[0013] Beneficial effects of this basic solution: Compared with traditional liquid phase reactions, rheological phase reactions show significant advantages in terms of condition setting. It cleverly avoids the need for harsh environments such as high temperature and strong alkali. This improvement not only greatly improves the safety performance of the reaction device, but also allows the entire reaction process to be carried out under milder and controllable conditions, thereby effectively reducing the safety risks that may be caused by extreme conditions, and also achieving efficient utilization and conservation of resources.
[0014] Furthermore, in step S1, the ferrous salt is ferrous chloride or ferrous sulfate.
[0015] Furthermore, in step S1, the ferrous salt is ferrous chloride, the mass ratio of sodium hydroxide powder, sodium dithionite and ferrous chloride is 1:1:1, and the mass ratio of the amount of deionized water to the mass of the solid mixture formed by mixing with sodium hydroxide powder, sodium dithionite and ferrous chloride is 0.3:1.
[0016] Furthermore, in step S2, the mass ratio of cobalt chloride hexahydrate to nano zero-valent iron environmentally friendly material is 4:1.
[0017] Furthermore, the temperature of the water bath condition in step S2 is 50-60°C.
[0018] Furthermore, in step S3, the reaction product is washed with oxygen-free distilled water, anhydrous ethanol or dilute hydrochloric acid until it becomes neutral.
[0019] Furthermore, the frequency of ultrasonic cleaning in step S3 is 30 kHz-50 kHz, and the power is 650 W-900 W.
[0020] Furthermore, the vacuum drying temperature in step S3 is 65-75°C.
[0021] The above-mentioned preparation method of magnetically controlled nano-cobalt-iron-based environmentally friendly materials is adopted, and a nano-zero-valent iron environmentally friendly material is prepared by a rheological phase method using a low sulfite solution as a reducing agent. The prepared nano-iron material is used as a reducing agent and reduced under liquid phase conditions to obtain a magnetically controlled nano-cobalt-iron-based environmentally friendly material.
[0022] The above-mentioned magnetron nano-cobalt-iron-based environmentally friendly material is used in recycling cobalt-containing wastewater and treating antibiotics. The magnetron nano-cobalt-iron-based environmentally friendly material after treating cobalt wastewater and antibiotics can be reused after being washed multiple times with hydrochloric acid.
[0023] The beneficial effects of the present invention are:
[0024] 1. The present invention discloses a method for preparing a magnetically controlled nano-cobalt-iron-based environmentally friendly material, wherein the substrate of the generated nanoparticles is zero-valent iron after the reaction; the rheological phase method is used, and the environmentally compatible low sulfite solution is used as a reducing agent to simultaneously complete the generation of the nano-zero-valent iron substrate and the modification of its surface sulfur to enhance its adsorption capacity and selectivity for antibiotic ions. The preparation method has a simple process, avoids the disadvantages of traditional methods such as toxic byproducts and harsh conditions, has low production costs, and has a wide range of raw material sources. It has the advantages of small investment and large output, and at the same time reduces the environmental hazards of the production process of traditional carbon-loaded reinforced heavy metal ion removal composite materials.
[0025] 2. The preparation method of a magnetically controlled nano-cobalt-iron-based environmentally friendly material disclosed in the present invention significantly improves the reactivity and pollutant elimination efficiency of zero-valent iron-based materials through a carefully designed metal surface modification strategy. This innovation not only greatly enhances the application potential of the material in sewage treatment, but also effectively removes high-concentration heavy metal ions, stubborn organic pollutants and chemical residues in wastewater, significantly reducing the difficulty of treatment and the risk of environmental pollution.
[0026] 3. The preparation method of a magnetically controlled nano-cobalt-iron-based environmentally friendly material disclosed in the present invention focuses on the sustainable use of resources from the source, and ensures the maximum benefit of raw material use through precise measurement and efficient recycling mechanism. During the reaction process, the raw materials and by-products that are not completely reacted can be reintroduced into the production process after proper treatment, forming a closed-loop cycle and reducing waste emissions.
[0027] 4. The preparation method of a magnetically controlled nano-cobalt-iron-based environmentally friendly material disclosed in the present invention cleverly uses nano-zero-valent iron as the core matrix, introduces an environmentally friendly low-sulfite solution as an efficient reducing agent through a carefully designed rheological phase process, and realizes the simultaneous construction of the nano-zero-valent iron substrate and the precise modification of the sulfur element on its surface, and finally obtains a nano-composite material with a unique layered structure. This composite material not only inherits the characteristics of nano-zero-valent iron as a powerful reducing agent, but also exhibits excellent capture and conversion capabilities for cobalt ions in a liquid environment, promotes the formation of cobalt-iron alloys, and provides a novel and efficient solution for the field of sewage treatment. It is particularly worth mentioning that the cobalt-iron alloy composite material prepared by this process, after completing its mission, can achieve convenient and efficient magnetic recycling and reuse by virtue of its excellent magnetic properties, significantly reducing the processing cost and reducing the environmental burden. The core advantage of the present invention is that it has significant cost-effectiveness, low investment threshold, and at the same time ensures the feasibility of large-scale production, opening up a new way to achieve more economical, efficient and environmentally friendly sewage purification and wastewater resource recovery.
[0028] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0030] Figure 1 This is a scanning electron microscope image of the magnetically controlled nano-cobalt-iron-based environmentally friendly material prepared in Example 1;
[0031] Figure 2 A schematic diagram showing the relationship between the removal rate of TC in wastewater and time when the magnetically controlled nano-cobalt-iron-based environmentally friendly material prepared in Example 1 removes simulated tetracycline (TC) wastewater with a concentration of 30 mg / l;
[0032] Figure 3 This is a recycling effect diagram of the magnetically controlled nano-cobalt-iron-based environmentally friendly material of the present invention;
[0033] Figure 4 This is a schematic diagram of the relationship between the TC removal rate in wastewater and time when the magnetically controlled nano-cobalt-iron-based environmentally friendly material prepared in Example 2 of the present invention removes simulated TC wastewater with a concentration of 50 mg / l. DETAILED DESCRIPTION
[0034] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0035] Example 1
[0036] Reference Figure 1-3 This embodiment provides a method for preparing a magnetically controlled nano-cobalt-iron-based environmentally friendly material, which specifically includes the following steps:
[0037] S1. In a glove box, weigh 20 g of granular sodium hydroxide powder (NaOH), 20 g of sodium dithionite (Na2S2O4) and 20 g of ferrous chloride, mix them evenly to obtain a solid mixture, stir them evenly, and then spray 20-25 ml of deionized water into the solid mixture with a spray bottle, stirring while spraying, so that the reactants react in the rheological phase, filter the cooled reaction product under nitrogen protection, and repeatedly ultrasonically wash the separated solid product with oxygen-free distilled water, anhydrous ethanol or dilute hydrochloric acid until it is neutral, to obtain nano zero-valent iron;
[0038] S2. In a water bath, pass nitrogen for 30 min, add a certain amount of cobalt chloride hexahydrate (CoCl2·6H2O), stir mechanically to fully dissolve, add the synthesized nano zero-valent iron, and keep heating and stirring to ensure that the cobalt salt is fully reduced by iron;
[0039] S3. After the reaction is complete, stirring is stopped, the reaction product is allowed to stand and cool to room temperature and then filtered under nitrogen protection. The separated solid product is washed with oxygen-free distilled water, anhydrous ethanol or dilute hydrochloric acid. The frequency of the ultrasonic cleaner is 30 kHz and the power is 650 W. The product is washed until the pH is neutral. After vacuum drying, the magnetically controlled nano-cobalt-iron-based environmentally friendly material is obtained.
[0040] The scanning electron microscope image of the magnetically controlled nano-cobalt-iron-based environmentally friendly material prepared in this embodiment is as follows: Figure 1 As shown, the morphological characteristics of magnetically controlled nano-cobalt-iron-based environmentally friendly materials were observed using a scanning electron microscope. Figure 1 The results showed that the nZVI particles formed a flake structure and the aggregation phenomenon was significantly reduced, while the magnetron nano-cobalt iron-based environmentally friendly materials showed a radial morphology. Further magnification and observation revealed that the magnetron nano-cobalt iron-based environmentally friendly materials showed a distinct rod-like structure with a length between 100 and 2000 nanometers and a thickness of less than 100 nanometers.
[0041] Prepare 500 ml of tetracycline (TC) simulated waste liquid with a concentration of 30 mg / L. Then, gradually dilute the stock solution according to the conditions of use, and take 100 mL of the stock solution into a 250 mL conical flask, then put the test tube into a constant temperature oscillator, set the temperature to 20°C, the speed to 200 r / min, and add a certain amount of magnetically controlled nano-cobalt iron-based environmentally friendly materials. Sampling was performed at certain intervals, and the water samples were filtered through a 0.22 μm filter membrane, and then measured using an ultraviolet spectrophotometer, and two sets of parallel experiments were performed to correct possible errors. When the TC content of each water sample no longer changed, it was confirmed that the adsorption was completed; the change of TC removal rate in wastewater over time is shown in the figure. Figure 2 As shown by Figure 2 It can be seen that TC in the wastewater was completely removed after 4 hours. After standing for 2 hours, the upper layer of the wastewater was clear, and the magnet-controlled nano-cobalt-iron-based environmentally friendly materials could be recycled and reused.
[0042] Reference Figure 3 , an experiment to recycle magnetron nano cobalt iron-based environmentally friendly materials. In order to realize the reuse of magnetron nano cobalt iron-based environmentally friendly materials, the following steps are taken to regenerate the materials after the reaction: first, the magnet is wrapped with plastic wrap to remove the used magnetron nano cobalt iron-based environmentally friendly materials, and then it is placed in a beaker filled with deionized water for 4 stirring and rinsing; then the same method is used to remove the washed materials and place them in hydrochloric acid. Figure 3 As a result, with the increase of regeneration times, the removal rate of TC gradually decreased, and the reduction range gradually expanded. After the fifth regeneration, the maximum removal rate of TC dropped to 63.63%, and the recycling performance of this material was outstanding.
[0043] Example 2
[0044] This embodiment provides a method for preparing a magnetically controlled nano-cobalt-iron-based environmentally friendly material, which specifically includes the following steps:
[0045] S1. Weigh 40 g of granular NaOH, 40 g of Na2S2O4 and 400 g of ferrous chloride in a glove box, mix them evenly to obtain a solid mixture, and then spray 40-45 ml of deionized water into the solid mixture with a spray bottle, stirring while spraying, so that the reactants react in the rheological phase, filter the cooled reaction product under nitrogen protection, and repeatedly ultrasonically wash the separated solid product with oxygen-free distilled water, anhydrous ethanol or dilute hydrochloric acid until it is neutral, to obtain a nano zero-valent iron material;
[0046] S2. In a water bath, pass nitrogen for 30 min, add a certain amount of cobalt chloride hexahydrate (CoCl2·6H2O), stir mechanically to fully dissolve, add the above-synthesized elemental iron, and keep heating and stirring to ensure that the cobalt salt is fully reduced by the iron;
[0047] S3. After the reaction is complete, stirring is stopped, the reaction product is allowed to stand and cool to room temperature and then filtered under nitrogen protection, the separated solid product is washed with oxygen-free distilled water, anhydrous ethanol or dilute hydrochloric acid, and repeatedly ultrasonically cleaned until neutral, the frequency of the ultrasonic cleaner is 30 kHz, the power is 650 W, and the pH is cleaned to neutral, and the magnetically controlled nano-cobalt-iron-based environmentally friendly material is obtained after vacuum drying.
[0048] Prepare 500 ml of tetracycline (TC) simulated waste liquid with a concentration of 50 mg / L. Then, gradually dilute the stock solution according to the conditions of use, and take 100 mL of the stock solution into a 250 mL conical flask, then put the test tube into a constant temperature oscillator, set the temperature to 20°C, the speed to 200 r / min, and add 1 g of magnetically controlled nano-cobalt-iron-based environmentally friendly material. Sampling was performed at certain intervals, and the water samples were filtered through a 0.22 μm filter membrane, and then measured using a UV-visible spectrophotometer, and two sets of parallel experiments were performed to correct possible errors. When the TC content of each water sample no longer changed, it was confirmed that the adsorption was completed; the change of TC removal rate in wastewater over time is shown in the figure. Figure 4 As shown by Figure 4 It can be seen that the removal rate of TC in the wastewater can reach 83.69% after 4 hours. After standing for 2 hours, the upper layer of the wastewater can be seen to be clear, and the magnetically controlled nano-cobalt-iron-based environmentally friendly materials can be recycled and reused using magnets.
[0049] Figure 3This is an experiment to recycle magnetron nano-cobalt iron-based environmentally friendly materials. In order to realize the reuse of magnetron nano-cobalt iron-based environmentally friendly materials, the following steps are taken to regenerate the materials after the reaction: first, use the magnet-wrapped plastic wrap method to take out the used magnetron nano-cobalt iron-based environmentally friendly materials, then put them into a beaker filled with deionized water and stir and rinse them 4 times; then use the same method to take out the cleaned materials and place them in hydrochloric acid. Figure 3 As a result, with the increase of regeneration times, the removal rate of TC gradually decreased, and the reduction range gradually expanded. After the fifth regeneration, the maximum removal rate of TC dropped to 56.98%. Figure 4 As shown, the material has outstanding recycling performance. By utilizing the strong magnetic properties of magnetically controlled nano-cobalt-iron-based materials, an efficient magnetic separation and recovery device is designed to achieve rapid separation and recycling of materials during the processing process. This not only simplifies the subsequent processing steps, but also greatly reduces material loss and operating costs, and builds a closed-loop resource circulation model.
[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a magnetically controlled nano-cobalt-iron-based environmentally friendly material, characterized in that: The following steps are involved: S1: In a glove box, sodium hydroxide powder, sodium dithionite and ferrous salt are taken, mixed evenly to obtain a solid mixture, and deionized water is sprayed. The mass ratio of sodium hydroxide powder, sodium dithionite and ferrous salt is 1~2:1~2:1, and the mass ratio of deionized water to the solid mixture is 0.3~0.5:
1. Nano-zero-valent iron is obtained under rheological phase conditions; S2: In a water bath, pass nitrogen for 30 min, add cobalt chloride hexahydrate, stir mechanically to fully dissolve, add nano zero-valent iron prepared in step S1, the mass ratio of cobalt chloride hexahydrate to nano zero-valent iron is 4-5:1, keep heating and stirring to ensure that the cobalt salt is fully reduced by iron; S3: After the reaction is complete, stirring is stopped, the cobalt salt reaction product that has been fully reduced by iron in step S2 is allowed to stand and cool to room temperature, and then filtered under nitrogen protection, the separated solid product is washed, repeatedly ultrasonically cleaned until neutral, and vacuum dried to obtain a layered magnetically controlled nano-cobalt-iron-based environmentally friendly material; S4: placing the magnetically controlled nano-cobalt-iron-based environmentally friendly material prepared in step S3 in an external magnetic field with a magnetic field strength of 300-800 kA / m to achieve separation of cobalt and iron, and further achieve magnetic recycling.
2. The method for preparing the magnetically controlled nano-cobalt-iron-based environmentally friendly material according to claim 1, characterized in that: In step S1, the ferrous salt is ferrous chloride or ferrous sulfate.
3. The method for preparing the magnetically controlled nano-cobalt-iron-based environmentally friendly material according to claim 2, characterized in that: In step S1, the ferrous salt is ferrous chloride, the mass ratio of sodium hydroxide powder, sodium dithionite and ferrous chloride is 1:1:1, and the mass ratio of deionized water to the mass of the solid mixture formed by mixing sodium hydroxide powder, sodium dithionite and ferrous chloride is 0.3:
1.
4. The method for preparing the magnetically controlled nano-cobalt-iron-based environmentally friendly material according to claim 1, characterized in that: In the step S2, the mass ratio of cobalt chloride hexahydrate to nano zero-valent iron environmentally friendly material is 4:
1.
5. The method for preparing the magnetically controlled nano-cobalt-iron-based environmentally friendly material according to claim 4, characterized in that: The temperature of the water bath condition in step S2 is 50-60°C.
6. The method for preparing the magnetically controlled nano-cobalt-iron-based environmentally friendly material according to claim 1, characterized in that: The reaction products in step S1 and step S3 are washed with oxygen-free distilled water, anhydrous ethanol or dilute hydrochloric acid until they are neutral.
7. The method for preparing the magnetically controlled nano-cobalt-iron-based environmentally friendly material according to claim 6, characterized in that: The frequency of ultrasonic cleaning in step S3 is 30 kHz-50 kHz, and the power is 650 W-900 W.
8. The method for preparing the magnetically controlled nano-cobalt-iron-based environmentally friendly material according to claim 7, characterized in that: The vacuum drying temperature in step S3 is 65-75°C.
9. A magnetically controlled nano-cobalt-iron-based environmentally friendly material prepared by the method for preparing a magnetically controlled nano-cobalt-iron-based environmentally friendly material according to any one of claims 1 to 8.
10. The use of the magnetically controlled nano-cobalt-iron-based environmentally friendly material as claimed in claim 9 in recycling cobalt-containing wastewater and treating antibiotics, wherein the magnetically controlled nano-cobalt-iron-based environmentally friendly material after treating cobalt wastewater and antibiotics can be reused after being washed multiple times with hydrochloric acid.
Citation Information
Patent Citations
Preparation method and application of core-shell structural magnetic nano composite catalyst
CN110215921A
Nitrogen-doped magnetic graphene oxide confinement iron-cobalt bimetallic monatomic composite material as well as preparation method and application of nitrogen-doped magnetic graphene oxide confinement iron-cobalt bimetallic monatomic composite material
CN114682289A
Method for preparing coated nano zero-valent iron loaded zinc-manganese-nickel composite material and co-producing ammonium dihydrogen phosphate from phosphated residues
CN117139636A
Process for separating and recovering precious metal by applying photocatalytic coupling technology
CN118581328A
Carbon nanotube ponytails
US20150321168A1